2023
DOI: 10.1002/ptr.7769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginger (Zingiber officinale) intake on human serum lipid profile: Systematic review and meta‐analysis

Abstract: Dyslipidemia is associated with an increased risk of cardiovascular events. Effect of ginger supplementation on lipid profile in humans remains controversial particularly in diabetic patients. A systematic search was performed covering PubMed, Medline, and Scopus, Web of Science (ISI), and Google scholar from January 2010 to January 2022. Inclusion criteria were randomized controlled clinical trials (RCT) study design, at least one of lipid profile components triglyceride (TG), total cholesterol (TC), lowdensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In terms of Zingiber officinale dose, the result of meta-regression found to be significant only for TC, so that increasing daily doses of ginger reduces TC levels by (β: -0.67; 95% CI: -1.28, -0.07; p = 0.028). They concluded that Zingiber officinale could be considered as an effective lipid lowering nutraceuticals [18].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of Zingiber officinale dose, the result of meta-regression found to be significant only for TC, so that increasing daily doses of ginger reduces TC levels by (β: -0.67; 95% CI: -1.28, -0.07; p = 0.028). They concluded that Zingiber officinale could be considered as an effective lipid lowering nutraceuticals [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the numbers and qualities of RCTs selected by each meta-analysis also varied. Table 35–64 provides an overview and perspective on some of these differences in methodologies among those trials assessed in meta-analyses.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…In general, there is more consistent evidence that ginger supplementation can decrease circulating blood levels of total cholesterol and triglycerides and increase high-density lipoprotein cholesterol levels. Evidence is less consistent for low-density lipoprotein cholesterol 10,12,13,56–58,62,63,80 …”
Section: Potential Health Benefitsmentioning
confidence: 99%
See 1 more Smart Citation